The Monroe Doctrine and Peruvian foreign policy: between suspicion and alignment (1900-1930) - Nieto Minaya, Willy Félix (2024)
The objective of this article is to analyze the role that the Monroe Doctrine played in the process of interaction and rapprochement between Peru and the United States during the period between 1900 and 1930. During this period, Peru implemented various strategies to approach the United States. United, seeking their intervention in their border dispute with Chile. Thus, Peruvian diplomats projected the Monroe Doctrine in their imaginaries, rhetoric, and foreign policy formulations, evidencing the significant influence of this ideological framework on the dynamics between Peru and the United States in the Pan American System. Two stages are distinguished that outlined the trajectory between Peru and the United States: an initial phase of rapprochement and elucidation of the doctrine (1900-1922), followed by a second phase of convergence (1923-1930).